Pemanfaatan Sistem Pelayanan Publik dalam Meningkatkan Hubungan Sosial: Studi Kasus di Kecamatan Cipadung, Bandung - M. Hafizh Irhab; Meli Fauziah (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2026)
This study aims to understand how public services in Cipadung Subdistrict, Bandung City, function not only as administrative processes but also as a way to build social relationships between the community and the government. The research uses a descriptive qualitative method, with data collected through in-depth interviews, direct observation, and documentation. The results show that digitalization has improved administrative efficiency, but access is still uneven, especially for elderly people and those with lower education levels. The gap in digital literacy creates barriers to accessing services fairly. On the other hand, programs such as “Obos” and “Sesah Hilapna” show that public services can also serve as a space for citizen participation and strengthen social unity. Public services in Cipadung demonstrate that service quality is not only about speed or efficiency, but also about how well the service reaches all groups in society fairly. Therefore, a more socially aware and inclusive approach is needed so that public services can function better and strengthen trust between citizens and the government.